1995
DOI: 10.1016/0014-5793(95)00227-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibition of cytosolic and membrane‐derived protein kinase C activity by staurosporine and other kinase inhibitors

Abstract: The hypothesis was tested that 9 kinase inhibitors with diverse specificities for protein kinase C (PKC), including staurosporine and four of its analogues, interfere differently with PKC derived from either the cytosolic or particulate fractions of MCF-7 breast carcinoma cells. GF 109203X inhibited the enzyme identically in either preparation. CGP 41251 and calphostin C inhibited cytosolic PKC more effectively than membrane-derived PKC with ratios of ICso (cytosolic PKC) over IC50 (membrane-derived PKC) of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 20 publications
4
17
0
Order By: Relevance
“…While this is a novel finding in regard to cardiac Lcl, Bourinet et al (1992) that both Cl-and delayed-rectifier K+ channels in these myocytes are regulated by one or more Ca2+ -dependent rather than Ca2+-independent PKC isoforms. In this regard, we note recent studies suggesting that H-7, the kinase inhibitor used in our tests, preferentially inhibits Ca2+-dependent (Ison et al, 1993), membrane-bound (Budworth & Gescher, 1995) PKC. Relation between PMA-induced 1c, and PKA-activated 'cl There is considerably more information available on the activation of cardiac Cl-channels by PKA than by PKC (Gadsby et al, 1995). Hume and colleagues (Levesque et al, 1993;Hume & Horowitz, 1995) have identified the cardiac Clchannel activated by PKA as an alternatively spliced variant of the cystic fibrosis transmembrane conductance regulating protein (CFTR) that is commonly found in epithelial cell membranes (e.g.…”
Section: Indications Of Ca2"-dependent Pkc Involvementsupporting
confidence: 55%
“…While this is a novel finding in regard to cardiac Lcl, Bourinet et al (1992) that both Cl-and delayed-rectifier K+ channels in these myocytes are regulated by one or more Ca2+ -dependent rather than Ca2+-independent PKC isoforms. In this regard, we note recent studies suggesting that H-7, the kinase inhibitor used in our tests, preferentially inhibits Ca2+-dependent (Ison et al, 1993), membrane-bound (Budworth & Gescher, 1995) PKC. Relation between PMA-induced 1c, and PKA-activated 'cl There is considerably more information available on the activation of cardiac Cl-channels by PKA than by PKC (Gadsby et al, 1995). Hume and colleagues (Levesque et al, 1993;Hume & Horowitz, 1995) have identified the cardiac Clchannel activated by PKA as an alternatively spliced variant of the cystic fibrosis transmembrane conductance regulating protein (CFTR) that is commonly found in epithelial cell membranes (e.g.…”
Section: Indications Of Ca2"-dependent Pkc Involvementsupporting
confidence: 55%
“…Of interest PKC-( of elderly subjects apparently dissociated from the particulate fraction and moved to the cytosol. PKC-( has been already demonstrated in the membrane of other cell types in the resting state [32] and that raises the possibility that this 'reverse translocation' may occur in other cells. We can not offer a conclusive explanation at this time.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have addressed the selectivity of staurosporine and its analogs to inhibit soluble PKC and membrane-associated PKC. Ro-31-8220, in particular, showed a striking selectivity for membrane-associated PKC, while GF109203X inhibited the soluble and membrane-associated forms of PKC to the same extent (35,36). Although all of these studies suggest that GF109203X is less selective for particular PKC isozymes than Ro-31-8220, the molecular reasons for these observations remain speculative.…”
Section: Discussionmentioning
confidence: 99%